PENGARUH CAPITAL INTENSITY TERHADAP TAX AGGRESSIVENESS DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Dewi Kusuma Wardani; Yusy Taurina (STIE Atma Bhakti, 2022)
This study was conducted to determine the effect of capital intensity on tax aggressiveness with profitability as a moderating variable. The population is manufacturing companies listed on the Indonesia Stock Exchange. Based on the quantitative research method with purposive sampling technique, in the 2016-2020 period, 53 companies were obtained with a total of 265 financial statement data minus 60 outlier data so that 205 financial statement data were obtained. The data analysis method is Multiple Regression Analysis and Moderated Regression Analysis (MRA). Based on the results of the study, capital intensity has no effect on tax aggressiveness and profitability cannot moderate the effect of capital intensity on tax aggressiveness.